DETERMINANTS OF GROWTH OF MUDHARABAH DEPOSITS IN SHARIA COMMERCIAL BANKS IN INDONESIA - Ana Mufidah; Novi Puspitasari; Sophis Melaty (STIE Mandala Jember, 2022)
The growth of mudharabah deposits is the level of deposit of funds by Islamic bankcustomers (creditors) for a certain period of time using the profit sharing principle. This studywill empirically examine the effect of profit sharing, financing to deposit ratio (FDR), netperforming loan (NPF), and bank size as independent variables (X) on the growth ofmudharabah deposits at Islamic Commercial Banks in Indonesia. 2016-2019 years. Thepopulation used in this thesis research is the entire population of Islamic Commercial Banks(BUS) in Indonesia and registered with the Financial Services Authority. The sample in thisstudy was all Islamic Commercial Banks in Indonesia, which amounted to 14 BUS in 2016-2019 with sensus method. The data analysis method used in this research is descriptivestatistical method with multiple linear regression analysis. The results of this study that theprofit sharing ratio (TBH) has no significant effect , The liquidity ratio (FDR) has asignificant effect , The NPF ratio has no significant effect and The bank size ratio (SIZE) hasa significant effect on the variable growth of mudharabah deposits (Y) at Islamic CommercialBanks in Indonesia.